Bovine WC1+ and WC1neg γδ T Lymphocytes Influence Monocyte Differentiation and Monocyte-Derived Dendritic Cell Maturation during In Vitro Mycobacterium avium Subspecies paratuberculosis Infection - Baquero, Monica M.; Plattner, Brandon L. (Frontiers in Immunology, 2017)
During early Mycobacterium avium subspecies paratuberculosis (Map) infection, complex interactions occur between the bacteria, cells from the mononuclear phagocytic system (MPS) including both resident (macrophages and dendritic cells) and recruited (monocytes) cells, and other mucosal sentinel cells such as γδ T lymphocytes. Though the details of early host-pathogen interactions in cattle remain largely underexplored, our hypothesis is that these significantly influence development of host immunity and ultimate success or failure of the host to respond to Map infection. The aims of the present study were to first characterize monocyte-derived MPS cells from young calves with respect to their immunophenotype and function. Then, we set out to investigate the effects of WC1+ and WC1neg γδ T lymphocytes on 1) the differentiation of autologous monocytes and 2) the maturation of autologous monocyte-derived dendritic cells (MDDCs). To achieve this, peripheral blood WC1+ or WC1neg γδ T lymphocytes were co-cultured with either autologous freshly-isolated peripheral blood derived monocytes or autologous immature MDDCs (iMDDCs). We began by measuring several markers of interest on MPS cells. Useful markers to distinguish monocyte-derived macrophages (MDMs) from MDDCs include CD11b, CD163 and CD172a which are expressed significantly higher on MDMs compared with MDDCs. Function, but not phenotype, was influenced by WC1neg γδ T lymphocytes: viability of Map harvested from monocytes differentiated in the presence of WC1neg γδ T lymphocytes (dMonWC1neg) was significantly lower compared to MDMs and MDDCs. With respect to DC maturation, we first showed that mature MDDCs (mMDDCs) have significantly higher expression of CD11c, CD80 and CD86 compared with iMDDCs and the phagocytic capacity of mMDDCs is significantly reduced compared to iMDDCs. We then showed that γδ T lymphocyte subsets induce functional (reduced phagocytosis) but not phenotypic (surface marker expression) iMDDC maturation. These data collectively show that γδ T lymphocytes influence differentiation, maturation and ultimately the function of monocytes during Map infection, which has significant implications on survival of Map and success of host defense during early Map infection.